FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENDERITA DIABETES MELLITUS DALAM MENJALANI PENGOBATAN DI PUSKESMAS PUDAK PAYUNG KOTA SEMARANG - Bella Oktaviani; Laksmono Widagdo; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Diabetes mellitus is a disease characterized by increased blood glucose levels exceeding normal and metabolic disorders of carbohydrates, proteins and fats are caused due to lack of insulin hormone. The problem of this research is health service at Puskesmas Pudak Payung which good enough but the number of Diabetes Mellitus patient still experience fluctuating number that is in year 2014 case number show 501 patient of Diabetes Mellitus then increase in 2015 840 cases, 2016terdapat 666 cases and in 2017 until month August alone as many as 395. The purpose of this study was to determine the factors associated with adherence of Diabetes Mellitus patients in treatment at Puskesmas Pudak Payung Kota Semarang. This research is a descriptive analytic research with research design used is cross sectional. The sample in this study is the people with Diabetes Mellitus in the work area of Puskesmas Puskesmas that is 76 people. The results of this study indicate the relationship between knowledge (p = 0.001), and tradition (p = 0.001) with adherence of Diabetes Mellitus patients in the treatment at Puskesmas Pudak Payung Kota Semarang and unrelated variables ie attitude (p = 0,539) (p = 1.004), infrastructure facilities (p = 0.115), support of health workers (p = 0.072), and family support (p = 0.578). Can be concluded factor of knowledge and tradition related to compliance of Diabetes Mellitus patient in undergoing treatment at Puskesmas Pudak Payung Semarang City.